IN SILICO STUDY OF ACTIVE COMPOUNDS IN Halosi (Bidens pilosa) AS ANDROGEN INHIBITORS IN PROSTATE CANCER - Harahap, Armansyah Maulana; Priawan, Indra; Siregar, Sarah Rahmayani (Current Biochemistry, 2025)
Prostate cancer is a disease that affects men's prostate gland cells and can spread to other parts of the body, mostly bones and lymph nodes. It is the third most common type of cancer in men in Indonesia and the second most common type of cancer in men worldwide. Ini adalah studi in silico tentang aktivitas chemical compounds in the leaves of the halosi plant (Bidens pilosa) to inhibit the Androgen receptor (1E3G) in the treatment of prostate cancer. Androgen receptor (AR) is a receptor protein that plays an important role in the development of prostate cancer cells. Molecular docking method using Chemdraw 3D, AutoDockTools 1.5.6., BIOVIA Discovery Studio 2021, and Ligandscout were used to conduct tests. Hasil menunjukkan bahwa bahan Bidens pilosa memiliki rendahnya ∆G free bond energy sebesar -10.26 KKal/mol and interaction with with several amino acid residues similar to Oxymetholone, a natural ligand. Therefore, it can be concluded that andrographolid compounds from halosi plant are the most able to inhibit Andorgen receptors